Annual cycles of diving behavior and ecology of the Weddell seal - Castellini, Michael Angelo; Davis, Randall William; Kooyman, Gerald L. (Berkeley, California University of California Pres, 1992)
Bulletin of the Scripps Institution of Oceanography, La Jolla, California ; v. 28
Keywords: California; oceanography; Weddell seal--Behavior--Antarctica.; Weddell seal--Behavior--Climatic factors--Antartica.; Weddell seal--Ecology--Antartica.